SOCIAL AND PSYCHOLOGICAL CORRELATES OF THE MAJOR SOURCES OF DISCOMFORT PERCEIVED BY STUDENTS IN THE COVID-19 PANDEMIC: AN EXPLORATORY STUDY ON A ROMANIAN SAMPLE - Éva KÁLLAY; Sebastian PINTEA (Studia Universitatis Babes-Bolyai, 2021)
The COVID-19 pandemic has a significant impact on the physical and psychologi-cal functioning of the entire world's population. Our study has had three major aims: (1) to identify the major sources of discomfort related to COVID-19 pan-demic in third year psychology students, (2) to establish a hierarchy of the major sources of discomfort, and (3) to identify possible vulnerabilities for different sources of discomfort. We used a cross-sectional study to explore more accurate-ly the individual reactions and possible vulnerabilities, also including open-ended questions to explore perceived sources of discomfort. Our study included 289 third-year psychology students from Babeș-Bolyai University in Cluj-Napoca, Romania (M=24.39 years, SD=7.12). All participants were assessed regarding their levels of: depression, narcissistic traits, perfection-ism, perceived stress, self-esteem, intolerance of uncertainty, subjective well‐being, and emotion regulation strategies. Our results indicate significant gender and age differences: male participants reported mobility restrictions as a source of discomfort more frequently than female participants, and younger students are less concerned with restrictions re-garding social relations, while older students report less emotional problems and less concern with educational problems. Students living in urban areas report less emotional problems than students from rural areas. The results generated by our research point out certain social and psychological vulnerabilities for each per-ceived source of discomfort (emotion-regulation strategies, perfectionism, nar-cissism), can bring a valuable input in counselling and therapy for individuals who are maximally affected by the pandemic of COVID-19. The authors had equal contributions to this study